A comparative study of (18)F-fluorodeoxyglucose positron emission tomography/computed tomography and (99m)Tc-MDP whole-body bone scanning for imaging osteolytic bone metastases - Zhang, Lin (BMC Med Imaging, 2015)
BACKGROUND: The objective of this study was to evaluate the feasibility and diagnostic value of (18)F-fluorodeoxyglucose positron emission tomography/computed tomography ((18)F-FDG PET/CT) and (99m)Tc-methylenediphosphonate (MDP) whole-body bone scanning (BS) for the detection of osteolytic bone metastases. METHODS: Thirty-four patients with pathologically confirmed malignancies and suspected osteolytic bone metastases underwent (18)F-FDG PET/CT and (99m)Tc-MDP whole-body BS within 30 days. The sensitivity, specificity, and accuracy with respect to the diagnosis of osteolytic bone metastases and bone lesions were compared between the two imaging methods. RESULTS: The sensitivity, specificity, and accuracy of (18)F-FDG PET/CT for the diagnosis of osteolytic bone metastases were 94.3% (95% confidence interval [CI], 91.6–96.2%), 83.3% (95% CI, 43.6–96.9%), and 94.2% (95% CI, 91.5–96.1%), respectively. It was found that (99m)Tc-MDP whole-body BS could discriminate between patients with 50.2% (95% CI, 45.4–55.1%) sensitivity, 50.0% (95% CI, 18.8–81.2%) specificity, and 50.2% (95% CI, 45.5–55.1%) accuracy. (18)F-FDG PET/CT achieved higher sensitivity, specificity, and accuracy in detecting osteolytic bone metastases than 99mTc-MDP whole-body BS (p<0.001). CONCLUSIONS: F-FDG PET/CT has a higher diagnostic value than (99m)Tc-MDP whole-body BS in the detection of osteolytic bone metastases, especially in the vertebra.